Cost- Effectiveness of Avatrombopag for the Treatment of Thrombocytopenia in Patients with Chronic Liver Disease - Mladsi D; Barnett C; Aggarwal K; Vredenburg M; Dieterich D; Kim R (Dove Medical Press, 2020)
Deirdre Mladsi,1 Christine Barnett,1 Kavita Aggarwal,2 Michael Vredenburg,2 Douglas Dieterich,3 Ray Kim4 1RTI Health Solutions Research, Triangle Park, NC, USA; 2Dova Pharmaceuticals, Durham, NC, USA; 3Icahn School of Medicine, New York, NY, USA; 4School of Medicine, Stanford University, Stanford, CA, USACorrespondence: Deirdre MladsiRTI Health Solutions Research, Triangle Park, NC 27709-2194 Tel +1 919 541 7094Fax +1 919 541 7222Email dmladsi@rti.orgBackground and Aim: Thrombocytopenia is common in people with chronic liver disease, who frequently undergo invasive procedures. To minimize the risk of bleeding, prophylactic platelet transfusions have traditionally been used but carry many risks. The aim of this study was to evaluate the cost-effectiveness of avatrombopag compared with platelet transfusion and lusutrombopag as a treatment for thrombocytopenia in adult patients with chronic liver disease scheduled to undergo a medical procedure.Methods: A decision-tree model was developed from a US payer perspective to capture acute events observed in phase 3 global randomized controlled clinical trials and, to support exploratory analyses, potential longer-term complications resulting from a major bleed or thromboembolic event. Treatment costs were taken from publicly available data sources. The interventions were evaluated in the overall trial populations and in subpopulations with higher and lower baseline platelet counts. Results were presented as incremental cost per platelet transfusion avoided. One-way and probabilistic sensitivity analyses were conducted.Results: In the overall population, avatrombopag reduced the need for platelet transfusions and produced cost-savings compared with platelet transfusion (80% fewer prophylactic platelet transfusions, $4250 lower costs) and lusutrombopag (42% fewer prophylactic platelet transfusions, $5819 lower costs). Similar results were seen in both the higher and lower platelet count subpopulations. The one-way and probabilistic sensitivity analyses found that the use of avatrombopag is cost-saving with the incremental cost-effectiveness ratio in quadrant IV (decreased costs, prophylactic platelet transfusions avoided).Conclusion: The use of avatrombopag is expected to be cost-saving while reducing the need for prophylactic platelet transfusions compared with platelet transfusion and lusutrombopag.Keywords: liver diseases platelet transfusion, thrombocytopenia, cost-effectiveness